Student perceptions of veterinary anatomy practical classes: a longitudinal study - Gummery, Erica; Cobb, Kate A.; Mossop, Liz H.; Cobb, Malcolm A. (University of Toronto Press, 2018)
Using cadaveric material to teach veterinary students poses many challenges. However, little research exists on the contribution of this traditional approach to student learning. This longitudinal study aimed to investigate student perceptions of cadaver-based anatomy classes in a vertically integrated veterinary curriculum at the University of Nottingham's School of Veterinary Medicine and Science. Likert-scale statements and free-text boxes were used in a questionnaire distributed to second-year veterinary students (response rate 59%, 61/103). The same questionnaire was subsequently distributed to the same cohort 2 years later, in the students' fourth year of study (response rate 68%, 67/98). Students agreed that cadaver-based activities aid their learning, and they particularly value opportunities to develop practical skills while learning anatomy. There are few changes in perception as undergraduates progress to clinical years of teaching. Students perceive anatomy to be important, and feel that their learning has prepared them for clinical placements. This study emphasizes the importance of using cadaveric materials effectively in anatomy teaching and, in particular, using clinical skills training to enhance the anatomy curriculum.